Design and Implementation of OLAP System for Distributed Data Warehouse - Murtadha Hamad; Abdullah Mahdi (Al-Rafidain Journal of Computer Sciences and Mathematics)
Data warehousing and on-line analytical processing (OLAP) are essential elements of decision support, which has increasingly become a focus of the database industry. A distributed OLAP system is designed which uses multi microcomputers based local area network. The introduction distributes technology into OLAP system that can disintegrate the complicated query and analysis into different servers. In this paper,  there are a lot of theoretical concepts associated with data warehouse and OLAP systems, and distributed data will be the implementation of several measures such as design cubic data and distribution algorithm and division of the data warehouse and decision support system DSS is performed to answer the complicated query. Practical results show that the distribution of data to multiple servers with OLAP system is faster according to the algorithm that has been dealing with client-server architecture to distribute the data warehouse. Statistical analysis concepts are used from current work to get predictable results which can be used to get suitable result DSS.